Evaluasi Sistem Informasi Rumah Sakit Ananda Purwokerto Menggunakan Domain Edm Dan Apo Cobit 5 - Ranggi Praharaningtyas Aji; Ito Setiawan; Yuliawan Adi Wibowo (JTIM : Jurnal Teknologi Informasi dan Multimedia, 2019)
Governance and planning for aligning business strategies with strategies in managing Information systems (SI) is the main key in winning business competition in each organization. Ananda Purwokerto General Hospital as a business organization engaged in health cannot be separated from this, but the problem of governance and the lack of alignment between the current business strategy and the SI strategy make the Ananda General Hospital Purwokerto less in terms of service issues. For this reason, an evaluation of the existing SI governance is needed at Ananda Purwokerto General Hospital. COBIT 5 can be used to evaluate SI governance, because in COBIT 5 there are 5 domains consisting of 2 categories, namely the category of governance domain and management domain, for problems experienced by Ananda Purwokerto General Hospital can use the EDM and APO domains on COBIT 5. The results expected are in the form of measuring the level of governance implementation of SIR Ananda Purwokerto General Hospital in the EDM and APO domains, so that the best recommendations can be given based on the COBIT 5 framework.